An Experimental Analysis of Waste Heat Recovery Potential from A Rotary Kiln of Cement Industry - Hussain, A.; Ali, M.; Sabir, M. S.; Ali, H. M.; Mehboob, M. (The Nucleus, 2020)
Cement production has been one of the most energy intensive processes in the world. Kilns serve as an integral part to produce clinker which is a tool to measure capacity of system. The temperature inside the kiln rises to 1400-1600 ºC while its surface temperature is between 200-400 ºC. The thermal efficiency of a kiln is about 55-60% and the remaining heat is lost in the form of flue gases and radiated from the surface. The current study has been carried out at a cement plant in Pakistan for the assessment of waste energy recovery from the surface of a rotary kiln. An experimental setup of small scale waste heat recovery with water heat exchanger has been fabricated at the plant site equipped with necessary instrumentation. Measurements of heat recovery are carried out at different water mass flow rates, surface temperatures, and transverse and radial distances of kiln. Results revealed that maximum water temperature achieved was 25 ºC at 1.8 kg/min mass flow rate of water at kiln surface temperature of 320 ºC. The distance of kiln and heat recovery unit is 380 mm where maximum potential from kiln surface is estimated to be 3.13 kW/m2. Thus, the current study proved significant waste heat recovery potential from kiln shell of a cement industry which can be further utilized for any on-site application.